On ∆-Convergence Theorems in b-CAT(0) Spaces: Cholatis Suanoom - Team, Support (Thai Journal of Mathematics, 2020)
In this work, we extend and improve CAT(0) spaces to b-CAT(0) spaces by using the concept of b-metric spaces. Second, we establish new spaces, that is b-CAT(0) spaces and prove the results of a fixed point for non-expansive mappings on b-CAT(0) spaces. Moreover, we obtain ∆-convergence theorems for non-expansive mappings on b-CAT(0) spaces and present some properties.